PENGARUH SUPLEMENTASI KONSENTRAT TEPUNG TONGKOL JAGUNG TERFERMENTASI YANG DITAMBAHKAN Zn-BIOKOMPLEKS TERHADAP KINERJA PERTUMBUHAN KAMBING KACANG - Nautus Stivano Dalle; Defiyanto Djami Adi; Elisabeth Yulia Nugraha; Hendrikus Demon Tukan; Paskalina Dewi Egi; Kamel Jemahu (Wahana Peternakan, 2023)
The study aimed at evaluating the effect of supplementing concentrate containing fermented corncob (TTJF) and Zn bio-complex on kacang goat performance. There were 12 kacang does 6-8 months of age with 9,3-15,5 averanging 11,20 kg and CV 13,30%. initial body weight used in the study. Completely randomized design 4 treatment diets offered were: R0 : concentrate feed without fermented corncob + 2,06g Zn bi-complex, R1 : concentrate feed containing TTJF 10% + Zn-Biokomplex 2,06g; R2 : concentrate feed containing TTJF 20% + Zn-Biokomplex 2,06g and R3: concentrate feed containing TTJF 30% + Zn-Biokomplex 2,06g. Data were analyzed using Analysis of Variance (ANOVA). The results of all variables measured were : R0 daily body weight gain (52.21g), R1 (66.16g), R2 (46.17g), R3 (42.09g), daily body length gain: R0 (0.17cm), R1 (0.20cm), R2 (0.18cm), R3 (0.14cm), daily girth cycle gain R0 (0.22cm), R1 (0.27cm), R2 (0.23cm), R3 (0.19cm) and daily body height R0 (0.15cm), R1 (0.18cm), R2 (0.15cm), R3 (0.13cm). Statistical analysis shows that the effect of supplementing containing fermented corncob concentrate with Zn bio-complex is not significant (P>0.05) on all performance variables measured. The conclusion is that supplementing containing fermented corncob concentrate up to 30% with Zn bio-complex performs the relative results in kacang does growth performances. Keywords: kacang goats, corncob, growth, Zn bio-complex